Coated metal mold
The coating mold with a hard coating of specific composition and surface characteristics addresses the issue of poor adhesion and durability in existing coating molds, achieving excellent durability under high load processing conditions.
Patent Information
- Application Number
- JP2024100601
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-22
- Filing Date
- 2024-06-21
- Publication Date
- 2025-04-04
AI Technical Summary
Coating molds with hard coatings formed by sputtering often experience poor adhesion between the mold and the hard coating, leading to reduced durability, especially under high load processing conditions.
A coating mold with a hard coating composed of nitrides, carbonitrides, oxides, or oxynitrides, where the Al content is 65 atom % or more, the Cr content is 15 atom % or more, and the total Al and Cr content is 80 atom % or more and 100 atom % or less, with a surface roughness Ra of 0.05 μm or less and a d value of 2.25 Å to 2.45 Å, enhancing adhesion and durability.
The described coating mold achieves excellent durability by ensuring strong adhesion between the mold and the hard coating, even under harsh conditions like cold forging, thereby extending the mold's lifespan.
Smart Images

Figure 2025051596000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated mold having a mold and a hard coating. [Background technology]
[0002] Dies such as punches used in forging, press working, etc. require not only hardness but also wear resistance in order to extend the life of the dies. Therefore, in order to improve the wear resistance of the dies, for example, a hard coating made of a nitride or carbonitride such as AlCr or AlCrSi is coated on the dies by physical vapor deposition or chemical vapor deposition, and at the same time, good surface smoothness is imparted to the hard coating.
[0003] For example, in Patent Document 1, a mold substrate is provided with an Al x Cr y S z Patent Document 1 describes a coated die for plastic working, characterized in that it is coated with a hard film made of a nitride of the above-mentioned. Specifically, Patent Document 1 describes that the wear resistance of the coated die for plastic working is improved by forming a hard film as smooth as possible on the working surface of the die by a sputtering method. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-284710 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when a hard film is formed by a sputtering method as in the method described in Patent Document 1, the raw material of the coating that is not ionized during film formation may reach the surface of the die, which is the base material, as it is. A coated die on which a film is formed in this way has poor adhesion between the die and the hard film. If a coated die having poor adhesion is used under high-load processing conditions such as cold forging, there is a problem with durability (i.e., die life) even if the hard film has good surface smoothness. Therefore, a coated die having a hard film is required to have further improved durability.
[0006] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a coated mold having excellent durability. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention includes the following preferred embodiments.
[0008] A coated mold according to a first aspect of the present invention comprises a mold and a hard coating formed on at least a portion of an outer surface of the mold, The hard coating contains a nitride, a carbonitride, an oxide, or an oxynitride of a metal element, In the total amount of the metal elements contained in the hard coating, the Al content is 65 atomic % or more, the Cr content is 15 atomic % or more, and the total content of Al and Cr is 80 atomic % or more and 100 atomic % or less, The surface roughness Ra of the hard coating is 0.05 μm or less, The d value resulting from the (111) plane of the face-centered cubic lattice of the hard coating is 2.25 Å or more and 2.45 Å or less.
[0009] A coated mold according to a second aspect of the present invention is the coated mold according to the first aspect, wherein the hard coating has a surface roughness Ra of 0.02 μm or less.
[0010] A coated mold according to a third aspect of the present invention is the coated mold according to the first or second aspect, wherein the hard coating is made of a nitride of a metal element, Of the total amounts of the metal elements contained in the hard coating, the Al content is 65 atomic % or more and 80 atomic % or less, the Cr content is 20 atomic % or more and 35 atomic % or less, and the total content of Al and Cr is 100 atomic %.
[0011] A coated die according to a fourth aspect of the present invention is the coated die according to any one of the first to third aspects, wherein the die is for use in cold plastic working.
[0012] A coated die according to a fifth aspect of the present invention is a coated die according to any one of the first to fourth aspects, wherein the die is a punch for plastically processing a workpiece by colliding with the workpiece.
[0013] A coated mold according to a sixth aspect of the present invention is a coated mold according to any one of the first to fifth aspects, wherein the material of the mold is an iron-based alloy or high-speed tool steel, and a base layer is provided between the mold and the hard coating. Effect of the Invention
[0014] According to the present invention, it is possible to provide a coated mold having excellent durability. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a schematic plan view for explaining the shape of a punch in an embodiment. [Diagram 2] FIG. 2 is an enlarged view of a portion E in FIG. [Diagram 3] FIG. 3 is a cross-sectional view for explaining an observation point of a covered punch after a cold forging test in an example. [Figure 4] FIG. 4 is a set of cross-sectional images showing the observation surfaces of the coated punch at each angle after the cold forging test in Example 1. [Diagram 5] FIG. 5 is a set of cross-sectional images showing the observation surfaces of the coated punch at each angle after the cold forging test in Example 2. [Figure 6] FIG. 6 is a set of cross-sectional images showing the observation surfaces of the coated punch at each angle after the cold forging test in Example 3. [Figure 7] FIG. 7 is a set of cross-sectional images showing the observation surfaces of the coated punch at each angle after the cold forging test in Comparative Example 1. [Figure 8] FIG. 8 is a set of cross-sectional images showing the observation surfaces of the coated punch at each angle after the cold forging test in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] As a result of intensive research by the present inventors, it has been found that in a coated mold having a mold and a hard coating formed on at least a portion of the outer surface of the mold, if the hard coating has a predetermined composition, a surface roughness Ra of a predetermined value or less, and a d value (i.e., interplanar spacing value) resulting from the (111) plane of a predetermined face-centered cubic lattice, a coated mold having excellent durability can be obtained.
[0017] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. Note that the scope of the present invention is not limited to the embodiment described here, and various modifications can be made without departing from the spirit of the present invention.
[0018] 1. Structure of the coated mold First, the configuration of the coated mold in this embodiment will be described. The coated mold has a mold and a hard coating formed on at least a part of the outer surface of the mold. In this specification, the "outer surface of the mold" means the surface portion of the mold that comes into contact with the workpiece when the mold is in use (i.e., the functional part). In other words, the hard coating may be formed on at least a part of the functional part of such a mold. These components will be described in detail below.
[0019] 1-1.Mold The type and shape of the mold are not particularly limited. For example, the mold may be an extrusion mold, a swaging mold, a punching mold, a coining mold, or various press molding molds. The material of the mold is also not particularly limited, and examples of the material include iron-based alloys (e.g., SKD (Steel Kogu Dice) material, SKS (Steel Kogu Special) material, etc.), high-speed tool steels (e.g., HSS (High Speed Steel) etc.), cemented carbide, various ceramics, etc.
[0020] Specifically, the die is not particularly limited, but is preferably a punch for plastically processing the workpiece by colliding with the workpiece. The type of punch is not particularly limited, and examples thereof include punches having a cross-sectional shape of a polygon such as a square or hexagon, an ellipse, a gear shape, etc., and punches having a shape corresponding to the inner diameter shape of a forged product. For example, a punch having a hexagonal cross-sectional shape can be used as a punch for forming bolts, nuts, etc. In addition, in this specification, the die may also include, for example, a plastic processing jig such as a punch or a pin, and a die used in combination with a punch, a punch, a pin, etc.
[0021] From the viewpoint of requiring particularly high durability, the die is preferably for cold plastic working. Furthermore, from the viewpoint of being used in a particularly harsh environment, among dies for cold plastic working, the die is preferably a die for cold forging. Specifically, tensile stress and compressive stress are repeatedly applied in a closed region and at a high speed (for example, 50 shots per minute or more) to the die for cold forging. Therefore, compared with other dies that can be used for various purposes, the die for cold forging is required to have high durability against repeated stress. By forming a hard coating described later on such a die for cold forging, the durability of the die can be more effectively improved and the die life can be extended.
[0022] 1-2.Hard coating In this embodiment, the hard coating is formed on at least a part of the outer surface of the mold by, for example, a method described later. The hard coating has a predetermined composition, a surface roughness Ra of a predetermined value or less, and a d value caused by the (111) plane of a predetermined face-centered cubic lattice. The details will be described below.
[0023] <Hard coating composition> The hard coating contains nitrides, carbonitrides, oxides, or oxynitrides of metal elements, and in the total amount of metal elements contained in the hard coating, the Al content is 65 atomic % or more, the Cr content is 15 atomic % or more, and the total content of Al and Cr is 80 atomic % or more and 100 atomic % or less. In this specification, the term "metal element" refers to a concept including not only metal elements but also metalloid elements that are optionally contained.
[0024] In this specification, the composition of the total amount of metal elements contained in the hard coating, such as the Al content, the Cr content, etc., means the average composition of the metal elements contained in the hard coating. The average composition of the metal elements contained in the hard coating can be measured by analysis using, for example, an energy dispersive X-ray spectrometer (EDS), as will be described in detail in the Examples below.
[0025] (Al and Cr) Nitrides, carbonitrides, oxides, or oxynitrides mainly composed of Al and Cr are film types that have an excellent balance between wear resistance and heat resistance, and also have excellent adhesion to the mold. In particular, by increasing the content ratio of Al in the nitrides, carbonitrides, oxides, or oxynitrides, an oxide protective film is easily formed on the surface of the hard film, and the hardness of the film is increased by finer structure of the hard film. Finer structure of the hard film means that the number of grain boundaries of the film increases. Disorders of atomic arrangement, that is, defects (point defects, line defects, and planar defects) exist in the film crystals. When stress is applied from the outside to the hard film during use of the mold, such defects move, which results in damage to the film. On the other hand, grain boundaries have the effect of stopping the movement of defects. Therefore, when the proportion of grain boundaries increases due to finer crystals, the movement of dislocations is suppressed, and as a result, the strength of the hard film can be improved. In this way, by increasing the Al content, an oxide protective film is more easily formed on the surface of the hard coating, thereby suppressing oxidative wear of the coating, and the hardness of the hard coating is increased by making the structure of the hard coating finer, thereby suppressing frictional wear of the coating, and in addition, the strength of the coating under external stress environments is improved.
[0026] The hard coating has an Al content of 65 atomic % or more in the total amount of metal elements contained in the hard coating. When the Al content is 65 atomic % or more, the above-mentioned effect of adding Al can be sufficiently exhibited. In the total amount of metal elements contained in the hard coating, the Al content is preferably 68 atomic % or more, more preferably 70 atomic % or more, and more preferably 75 atomic % or more.
[0027] On the other hand, if the Al content is too high, the hardness of the hard coating may decrease, so the Al content is preferably 80 atomic % or less of the total amount of metal elements contained in the hard coating, and more preferably 78 atomic % or less of the total amount of metal elements contained in the hard coating.
[0028] The hard coating has a Cr content of 15 atomic % or more in the total amount of metal elements contained in the hard coating. If the Cr content is 15 atomic % or more, a uniform and dense oxidation protective film is easily formed on the surface of the hard coating formed on the coated mold during use of the coated mold in this embodiment, and damage to the hard coating is easily suppressed. In the total amount of metal elements contained in the hard coating, the Cr content is preferably 18 atomic % or more, more preferably 20 atomic % or more, and even more preferably 22 atomic % or more.
[0029] On the other hand, if the Cr content is too high, it becomes difficult to obtain the above-mentioned effect of increasing the Al content, so in the total amount of metal elements contained in the hard coating, the Cr content is 35 atomic % or less, preferably the Cr content is 32 atomic % or less, and more preferably the Cr content is 30 atomic % or less.
[0030] In the hard coating, the total content of Al and Cr is 80 atomic % or more and 100 atomic % or less in the total amount of metal elements contained in the hard coating. When the total content of Al and Cr is 80 atomic % or more and 100 atomic % or less, excellent durability can be imparted to the coated mold. The total content of Al and Cr is preferably 85 atomic % or more, more preferably 90 atomic % or more, even more preferably 95 atomic % or more, and even more preferably 100 atomic %.
[0031] The hard coating includes a nitride, carbonitride, oxide, or oxynitride of the above-mentioned metal element. From the viewpoint of being a film type with superior heat resistance, the hard coating is preferably a nitride of a metal element.
[0032] Specifically, one example of such a hard coating is made of a nitride of a metal element, and in the total amount of metal elements contained in the hard coating, the Al content is from 65 atomic % to 80 atomic %, the Cr content is from 20 atomic % to 35 atomic %, and the total content of Al and Cr is preferably 100 atomic %.
[0033] (Metal elements other than Al and Cr) The hard coating may contain metal elements other than Al and Cr within a range that does not significantly reduce the durability of the coated mold. For example, the hard coating may contain at least one metal element selected from the group consisting of elements of Groups 4a, 5a, and 6a of the periodic table (Groups 4, 5, and 6 in the long-form periodic table) and Si, B, Y, Yb, and Cu, for the purpose of improving properties such as wear resistance, heat resistance, and durability (hereinafter also referred to as "coating properties"). Among these elements, Si and B are examples of semimetal elements among metal elements. These elements can generally be contained in order to improve the coating properties of the hard coating. If the content of metal elements other than Al and Cr is too large, the durability of the coated member may be reduced. Therefore, when the hard coating contains metal elements other than Al and Cr, the total content is preferably 20 atomic % or less of the total amount of metal elements contained in the hard coating.
[0034] <Surface roughness Ra (arithmetic mean height) of hard coating> In this embodiment, the surface roughness Ra of the hard coating is 0.05 μm or less. In this specification, the "surface roughness Ra of the hard coating" means the arithmetic mean height Ra measured using a surface roughness measuring device in accordance with JIS-B-0601 (2001), as will be described in detail in the examples below.
[0035] When the surface roughness Ra of the hard coating is 0.05 μm or less, the hard coating has good surface smoothness, and as a result, a coated mold having excellent durability can be obtained. The surface roughness Ra of the hard coating is preferably 0.03 μm or less, more preferably 0.02 μm or less, and even more preferably 0.015 μm or less.
[0036] The surface roughness Ra of the hard coating can be easily reduced to a low value of 0.05 μm or less without post-treatment for surface smoothing such as polishing after the formation of the hard coating, for example, by forming the hard coating by an arc ion plating method using a film formation device equipped with a permanent magnet, a filter mechanism, etc., as described later. Specifically, by forming the hard coating by such an arc ion plating method, adhesion of macroparticles (droplets) to the mold during the film formation is reduced, and a hard coating having remarkably excellent surface smoothness is formed. As a result, a coated mold having excellent durability can be obtained.
[0037] <d value caused by the (111) plane of the face-centered cubic lattice of the hard coating> In this embodiment, the d value due to the (111) plane of the face-centered cubic lattice of the hard coating (hereinafter also simply referred to as the "d value of the hard coating") is 2.25 Å (angstroms) or more and 2.45 Å or less. If the d value of the hard coating is smaller than 2.25 Å, the stress in the coating is too high, so the coating is likely to peel off from the substrate. If the d value of the hard coating is larger than 2.45 Å, the coating stress is too low, so the coating life is shortened. Therefore, the d value of the hard coating is preferably 2.25 Å or more and 2.45 Å or less. As a result, a coated mold having excellent durability can be obtained. The d value of the hard coating is preferably 2.30 Å or more, and more preferably 2.35 Å or more. In addition, the d value of the hard coating is preferably 2.43 Å or less, and more preferably less than 2.40 Å.
[0038] In this specification, the "d value due to the (111) plane of the face-centered cubic lattice of the hard coating" means a value obtained by a method described in detail in the following examples. Specifically, the d value due to the (111) plane of the face-centered cubic lattice of the hard coating can be obtained by identifying the crystal structure of the hard coating using an X-ray analyzer and performing a peak search in the obtained X-ray peak profile. More specifically, the d value due to the (111) plane of the face-centered cubic lattice of the hard coating in this specification means the d value of the (111) plane of the cubic crystal structure calculated according to the Bragg formula of the following formula (1) by determining the diffraction angle of the peak due to the (111) plane of the face-centered cubic lattice of chromium nitride (CrN). In the following formula (1), d: interplanar spacing, λ: X-ray wavelength (1.5406 Å), and θ: X-ray diffraction angle.
number
[0039] The d value of the hard coating can be set to 2.25 Å or more and 2.45 Å or less, for example, by forming the hard coating by a general arc ion plating method.
[0040] <Hard coating thickness> The hard coating in this embodiment is not particularly limited, but is preferably 4 μm or more. When the thickness of the hard coating is 4 μm or more, the durability of the hard coating against stress can be further improved, and a coated mold having superior durability can be obtained.
[0041] In this specification, the "thickness of the hard coating" means a value calculated by measuring the dimensional change before and after the formation of the hard coating, as will be described in detail in the Examples below.
[0042] The thickness of the hard coating is more preferably 5 μm or more, and even more preferably 6 μm or more. The upper limit of the thickness of the hard coating is not particularly limited, but for example, the thickness of the hard coating is preferably 10 μm or less, and more preferably 8 μm or less.
[0043] As described above, the coated die in this embodiment has excellent durability and can be suitably applied to, for example, punches for cold forging used in harsh environments.
[0044] 2. Other configurations of coated molds In the coated mold of this embodiment, in order to further improve the adhesion between the mold and the hard coating, a base layer may be provided between the mold and the hard coating as necessary. In particular, when the material of the base material of the mold is an iron-based alloy (e.g., SKD material, SKS material, etc.) or high-speed tool steel (e.g., HSS, etc.), it is preferable to provide a base layer between the mold and the hard coating from the viewpoint of reliably suppressing the risk of coating peeling due to the material of the base material. The base layer can be formed, for example, from any one or more layers of a hard coating containing a nitride, carbonitride, oxide, or oxynitride of a metal element that does not satisfy the above-mentioned conditions of the hard coating, a metal, a nitride, a carbonitride, and a carbide. Furthermore, as long as the durability of the above-mentioned hard coating is not impaired, one or more layers made of the above-mentioned material may be formed on the hard coating formed on the outer surface of the mold.
[0045] In this embodiment, a hard coating (hereinafter referred to as a "second hard coating") having a different composition and / or physical properties from the first hard coating but satisfying the above-mentioned conditions of the hard coating may be formed on the hard coating (hereinafter referred to as a "first hard coating") formed on the outer surface of the mold. Furthermore, a further hard coating (hereinafter referred to as a "third hard coating") satisfying the above-mentioned conditions of the hard coating may be formed on the coating formed by laminating these. Furthermore, such a first hard coating and a second hard coating (or a first hard coating, a second hard coating, and a third hard coating) may be mutually laminated. Alternatively, the first hard coating and the second hard coating (or a first hard coating, a second hard coating, and a third hard coating) may be alternately laminated in two or more layers. Alternatively, as long as the durability of the hard coating described above is not impaired, one or more layers of a hard coating containing a nitride, carbonitride, oxide or oxynitride of a metal element that does not satisfy the conditions of the hard coating described above, a metal, a nitride, a carbonitride and a carbide may be sandwiched between the laminated structure of a plurality of such hard coatings of the present embodiment.
[0046] When one or more of such underlayers, upper layers and / or different hard coatings are formed, the total thickness of the laminate is preferably 10 μm or less, although there are no particular limitations thereon.
[0047] 3. Manufacturing method of coated mold The coated mold in this embodiment can be manufactured by coating (forming) a hard film on at least a part of the outer surface of the mold. Sputtering or arc ion plating can be applied to the coating of the hard film. In the sputtering method, in addition to nitrogen gas, which is a reactive gas, argon gas is introduced to sputter the target during film formation. Argon gas, which is an inert gas, does not react with the sputtered metal particles and is not included in the film. However, since ionized argon collides with energy against a base material (mold) to which a negative voltage is applied, some argon may be mixed into the film at this time. If some argon is mixed into the film, defects will occur in the film, which may cause a decrease in the strength of the film. Therefore, when a hard film is formed by sputtering on a mold used under high load conditions, the life of the manufactured coated mold may be shortened. Therefore, it is preferable to apply the arc ion plating method to coat the mold with a hard film. In the arc ion plating method, it is preferable to use a film forming apparatus equipped with a cathode having permanent magnets disposed on the rear surface and outer periphery of the target.
[0048] The deposition apparatus in the arc ion plating method includes, for example, an arc evaporation source having a target which is a material of the hard coating, an anode which is a destination of electrons during arc discharge, an arc power source for inputting an arc current to the target, a furnace (vacuum container) which contains a mold which is a substrate, a substrate rotation mechanism for rotating the substrate in the furnace, a bias power source for applying a bias voltage to the substrate, a heater for heating the inside of the furnace and the substrate, a vacuum pump for creating a vacuum in the furnace, and a gas inlet for introducing both or either of an inert gas (helium, neon, argon, krypton) and a reactive gas (nitrogen, hydrocarbon, oxygen) into the furnace. In addition, the deposition apparatus preferably includes a filter mechanism capable of reducing macroparticles (droplets) which are clumps of the coating material by a magnetic field.
[0049] The film formation method will be described in detail below. First, the inside of the furnace is evacuated to a vacuum. At that time, the vacuum pressure is 10×10 -3 It is preferable to evacuate the chamber to a pressure of 5×10 Pa or less. -3 Pa or less is more preferable, and 1×10 -3 It is more preferable that the pressure is equal to or less than 100 Pa. By applying a vacuum pressure, it is possible to prevent oxidation of the substrate, which would otherwise occur when heating of the substrate is started in a state where there is a large amount of residual gas in the furnace.
[0050] After evacuation, the substrate is heated. The substrate temperature is preferably 400° C. to 550° C., more preferably 420° C. to 520° C., and even more preferably 450° C. to 500° C. By heating the substrate at a temperature within this range, it is possible to prevent a decrease in film adhesion due to insufficient diffusion at the substrate-film interface caused by an excessively low temperature, and also to prevent the substrate material from being softened by heat.
[0051] Next, the substrate is etched. The etching process can be performed by introducing an inert gas into the furnace, turning the inert gas into plasma, and colliding the inert gas ions with the substrate to which a negative bias voltage is applied. Alternatively, the mounted arc evaporation source can be discharged together with an inert gas, and the metal target attached to the arc evaporation source and the inert gas can be ionized and collided with the substrate to perform the etching process. When the arc evaporation source is discharged without using an inert gas, the etching process can be performed only with metal ions. When an inert gas is used, the pressure inside the furnace is preferably 0.1 Pa to 5 Pa. When the inert gas pressure is too low, the amount of inert gas ions generated is small, so that a sufficient etching effect may not be obtained. On the other hand, when the inert gas pressure is too high, the ionized inert gas may collide with the non-ionized inert gas, and a sufficient etching effect may not be obtained. When the metal target is ionized by discharging the arc evaporation source to perform the etching process, the arc current is preferably 50 A to 150 A. If the arc current is too low, it becomes difficult to generate an arc discharge, and sufficient etching may not be possible. On the other hand, if the arc current is too high, a large number of ions may be generated, improving the etching effect, but a large number of droplets (macroparticles) formed by melting a part of the target may be generated, and the macroparticles may adhere to the substrate surface, causing the substrate surface to become rough. Since the surface roughness Ra of the hard coating is affected by the roughness of the substrate (mold), it is preferable to have a low arc current in order to suppress the generation of macroparticles from the viewpoint of obtaining a desired surface roughness Ra of the hard coating. From the viewpoints of both a sufficient etching effect and suppression of the generation of macroparticles, the arc current is preferably 50A to 150A. In addition, in order to reduce the adhesion of the generated macroparticles to the substrate, it is preferable that the arc evaporation source provided in the film forming apparatus is equipped with a filter mechanism using a magnetic field. A negative bias voltage is applied to the substrate during etching, and from the viewpoint of obtaining a sufficient etching effect, the applied voltage is preferably -100V to -1000V.If the bias voltage applied to the substrate is too low, a sufficient etching effect may not be obtained, whereas if the voltage is too high, abnormal discharge may occur on the substrate surface, damaging the substrate.
[0052] After the etching process, a hard film is formed on the substrate. When forming the film, a reactive gas is introduced into the furnace. In order to stabilize the discharge, an inert gas may be mixed with the reactive gas. However, the inert gas may remain in the film without reacting with the evaporated metal material, and may ultimately cause film defects. Therefore, when forming a hard film by mixing a reactive gas and an inert gas, the amount of the inert gas remaining in the hard film is preferably less than 5%, more preferably less than 1%. In this specification, the amount of the inert gas remaining in the hard film is the amount measured by using an Oxford Instruments EDS (detector: X-act C3400, analysis software: INCA) attached to a scanning electron microscope (Hitachi High-Tech Fielding, S-3400N). The reactive gas may be selected from, for example, nitrogen gas, oxygen gas, and hydrocarbon gas such as methane according to the purpose. For example, when forming nitrides of Al and Cr, nitrogen may be introduced into the furnace as a reactive gas. In order to form a hard coating containing dense nitrides with excellent strength, the pressure in the furnace during film formation is preferably 1 Pa to 10 Pa, more preferably 2 Pa to 8 Pa, and even more preferably 4 Pa to 6 Pa. If the pressure is too low, the reaction between the evaporated metal and the reactive gas may be insufficient, and the desired nitride may not be formed. On the other hand, if the pressure is too high, the evaporated metal ions may collide with the reactive gas, and these ions may reach the substrate in a state of losing energy. As a result, these ions may not be able to diffuse sufficiently on the substrate surface, and a dense coating may not be formed, which may cause a decrease in coating strength. It is preferable that the absolute value of the negative bias voltage applied to the substrate is gradually increased from the vicinity of the substrate to the vicinity of the surface of the hard coating. For example, it is preferable that the absolute value of the negative bias voltage applied to the substrate is gradually increased from the vicinity of the substrate to the vicinity of the surface of the hard coating in the range of -50 V to -200 V. If the bias voltage is too low, soft hexagonal crystal structured AlN (aluminum nitride) will precipitate in the coating, which may lead to a decrease in the hardness of the hard coating.On the other hand, if the bias voltage is too high, the energy of metal ions and gas ions that are pulled by the negative voltage and collide with the substrate increases, which may increase the effect of striking the coating deposited on the substrate (ion peening effect). As a result, the distortion of the coating may increase, causing an increase in stress. If the stress increases too much, it may cause the coating to peel off. Therefore, in order to suppress peeling on the substrate and form a coating with high hardness, it is preferable to set the bias voltage during film formation to -50V to -200V.
[0053] It is also preferable to gradually increase the arc current applied to the target from the vicinity of the substrate to the vicinity of the surface of the hard coating. For example, it is preferable to gradually increase the arc current applied to the target from the vicinity of the substrate to the vicinity of the surface of the hard coating within a range of 50 A to 200 A.
[0054] As described above, by forming a hard film by the arc ion plating method using a film forming device equipped with such a permanent magnet, a filter mechanism, etc., a hard film having excellent surface smoothness can be easily obtained. In addition, by varying the absolute value of the negative bias voltage applied to the substrate and the arc current passed through the target as described above, it is possible to control the crystal structure of the hard film to be different between the vicinity of the substrate (the vicinity of the mold) and the vicinity of the surface. As a result, the crystals of the finally obtained hard film have a cubic structure with a (111) or (200) plane orientation, and the d value of the interplanar spacing of the (111) plane can be set to 2.25 Å or more and 2.45 Å or less. In other words, by using such an arc ion plating method, it is possible to more easily form a hard film that satisfies the above-mentioned conditions of the surface roughness Ra of the hard film and the d value of the cubic (111) plane. EXAMPLES
[0055] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0056] 1. Formation of a hard film on the punch used as a die In Examples 1 to 3 and Comparative Examples 1 and 2, coated dies for cold forging (hereinafter also referred to as "coated punches") in which a hard coating was formed on a punch serving as a die were actually manufactured, and various physical properties of the hard coating were measured and calculated, while the durability of the coated punches was evaluated.
[0057] The details of the measurement and calculation methods for various physical properties of the hard coating and the die (punch) used are as follows.
[0058] [Method for measuring the average composition of metal elements contained in hard coating] Using an Oxford Instruments EDS (detector: X-act C3400, analysis software: INCA) attached to a scanning electron microscope (Hitachi High-Tech Fielding, S-3400N), the coating section of the Calotest mark cross section was measured under conditions of an acceleration voltage of 15 kV, a live time of 50 s, and repeated four times to calculate the average composition of metal elements contained in the hard coating. The average composition of argon gas contained in the hard coating was also measured in the same manner.
[0059] [How to calculate the thickness of the hard coating] The thickness of the hard film was calculated by measuring the dimensional change before and after the formation of the hard film using a micrometer (manufactured by Mitutoyo Corporation).
[0060] [How to calculate the d value of hard coating] The d value of the hard film was determined by first identifying the crystal structure of the hard film under the following condition (1) using an X-ray analyzer (Rigaku Corporation, "SmartLab"). Then, a peak search was performed on the obtained X-ray peak profile under the following condition (2). Specifically, the diffraction angle of the peak due to the (111) plane of the face-centered cubic lattice of chromium nitride (CrN) was determined, and the interplanar spacing d value of the (111) plane of the cubic crystal structure was calculated according to the Bragg formula in the above-mentioned formula (1). (1) X-ray diffraction measurement conditions Target: Cu Target output: 40kV-40mA 45kV-200mA Filter: Kβ filter Incident Monochrome: CBO Unit (Cu&Co) Counter monochromator: Not used Counter: Scintillation counter Slit: Divergence: 1mm, Divergence vertical limit: 10mm, Scattering: Open, Receiving: Open Scanning speed: 1° / min Sampling width: 0.01° Scan axis: 2θ / θ Measurement angle (2θ): 30°~46° θ offset: 0° Number of times accumulated: 1 (2) Peak search conditions Method: Second order differential method Peak width threshold: 0.25° Peak intensity threshold: 50cps
[0061] [Method of measuring surface roughness Ra of hard coating (immediately after hard coating formation or after polishing (after post-treatment))] The surface roughness Ra (arithmetic mean height) of the hard coating was measured using a surface roughness / contour shape composite measuring instrument (Surfcom NEX, manufactured by Tokyo Seimitsu Co., Ltd.) in accordance with JIS-B-0601 (2001). Specifically, a coated punch was placed on a sample stage, and the surface roughness of the functional part of the punch substrate on which the hard coating was formed was measured under the following conditions. The surface roughness Ry (maximum height) of the hard coating, as well as the surface roughness Ra and surface roughness Ry of the punch surface before the hard coating was formed, were also measured using the same method. ·conditions Measurement type: Roughness measurement Cutoff type: 2RC Tilt correction: least squares linear correction Measurement length: 1.3 mm Cutoff wavelength: 0.25mm Measurement magnification: 10,000x Measurement speed: 0.15mm / sec
[0062] [Mold] The die used was a punch for cold forging and forward extrusion. Specifically, a punch made of cemented carbide according to the CIS standard VC30 (CIS019D classification) was used. More specifically, the cemented carbide material was subjected to grinding and cutting to have the following shape, thereby producing a punch for the experiment.
[0063] FIG. 1 shows a schematic plan view for explaining the shape of the punch in the embodiment. The punch 1 shown in FIG. 1 has a substantially cylindrical shape. As shown in FIG. 1, the punch 1 includes a functional part 2, which is a part that contacts the workpiece during forging, and a gripping part 3 having a length C for being gripped by a forging device. The upper end part 4 is the tip end surface of the functional part 2. Specifically, the length L of the functional part 2 is 116 mm in the longitudinal direction of the punch 1, and the length C of the gripping part 3 is 260 mm. More specifically, by performing grinding and cutting, as shown in FIG. 2, which is an enlarged view of part E in FIG. 1, the tip diameter L1 of the punch 1 is 24.65 mm, the relief diameter (diameter) L2 is 24.5 mm, the arc radius of the arc shape formed from the tip point P1 is 1.5 mm, the relief angle α is 1.5°, and the tip angle β of the upper end part 4 is 9°. Overall, as shown in Figs. 1 and 2, the tip diameter L1 of the punch 1 and the diameter-reduced portion along the longitudinal direction of the punch 1 are connected in a smooth arc shape.
[0064] After grinding and cutting, the outer surface of the functional part 2, including the upper end part 4 on which a hard coating will be formed later, was mirror-polished so that the surface roughness Ra (arithmetic mean height) was 0.03 μm or less and the surface roughness Ry (maximum height) was 0.3 μm or less.
[0065] Thereafter, hard coatings were formed on the punches thus prepared by different methods to produce coated punches in Example 1 and Comparative Example 1. The manufacturing methods for each coated punch will be described in detail below.
[0066] Example 1 In Example 1, a hard coating was formed on a punch using a coating device equipped with a permanent magnet and a filter mechanism, and a coated punch was manufactured. The configuration of the coating device and a specific method for forming the hard coating are described below.
[0067] [Film forming equipment] A film-forming apparatus using an arc ion plating method was used to form (form) a hard film on the surface of the substrate (the surface of the functional part of the punch in this Example 1). The detailed configuration of this film-forming apparatus is as follows. The film-forming apparatus has a plurality of cathodes (arc evaporation sources), a vacuum vessel, and a substrate rotation mechanism. The cathode is provided with an electromagnetic coil for converging plasma in front of the target, and a permanent magnet is provided on the back of the target. The cathode also has a filter mechanism that can reduce droplets by a magnetic field. The inside of the vacuum vessel can be evacuated by a vacuum pump, and gas can be introduced into the vacuum vessel through a supply port provided in the vacuum vessel. A bias power supply can be connected to the substrate placed in the vacuum vessel, and a negative bias voltage can be applied independently to the plurality of substrates. The substrate rotation mechanism has a work table, a plate-shaped jig attached to the work table, and a pipe-shaped jig attached to the plate-shaped jig. In the substrate rotation mechanism, the work table rotates at a speed of 1.5 revolutions per minute. The plate-shaped jig and the pipe-shaped jig are each capable of rotating and revolving.
[0068] [Heating and evacuation process (pre-deposition process)] First, the functional part of the punch as the substrate was fixed to a pipe-shaped jig in the vacuum chamber of the film-forming apparatus, and the pre-film-forming process was carried out as follows. -3 The vacuum chamber was then evacuated to a vacuum of less than 50 Pa. The heater installed in the vacuum chamber was then used to heat the punch's functional part until the temperature reached 500°C, and the chamber was then evacuated to a vacuum. -3 Pa or less.
[0069] [Ar bombardment process (pre-deposition process)] Thereafter, Ar gas was introduced into the vacuum chamber, a current was passed through the filament to generate Ar ions, and a negative bias voltage was applied to the functional part of the punch to perform Ar bombardment.
[0070] [Film forming process] After Ar bombardment, the gas in the vacuum chamber was replaced with nitrogen, and the pressure in the vacuum chamber was set to 4 Pa. Electricity was supplied to the cathode, and a negative bias voltage was applied to the functional part of the punch, which was the substrate, to form an Al and Cr nitride (hard film) of about 5 μm. In this Example 1, a cathode having an Al content of 75 atomic % and a Cr content of 25 atomic % was used. The bias voltage was changed (graded) in the range of -70 V to -200 V so that its absolute value gradually increased from the vicinity of the functional part of the punch of the hard film (near the substrate) to the vicinity of the surface. The arc current was also changed (graded) in the range of 70 A to 180 A so that its value gradually increased from the vicinity of the functional part of the punch of the hard film (near the substrate) to the vicinity of the surface.
[0071] For the coated punch of Example 1 thus produced, various physical properties of the hard coating after coating formation were measured and calculated by the above-mentioned methods.
[0072] Finally, as a preparation for a durability test of the coated punch described later, the outer surface of the functional part of the coated punch in Example 1 was mirror-polished again to adjust the surface roughness Ra of the functional part of the coated punch to 0.05 μm or less (more specifically, the surface roughness Ra was 0.03 μm) and the surface roughness Ry to 0.5 μm or less. The measurement and calculation results, as well as the surface roughness values after polishing (after post-treatment) (after hard coating formation) are summarized in Table 1 described later.
[0073] The durability of the coated punch was evaluated as follows: The evaluation results of the coated punch in Example 1 will be summarized later together with those of other Examples and Comparative Examples.
[0074] [Method for evaluating the durability of coated punches] The coated punch was used as a cold forging die (for forward extrusion) to evaluate durability. The cold forging former used and other cold forging test conditions are as follows. The durability was evaluated by observing the exposed base material of the cross section of the coated punch (specifically, the functional part of the coated punch) shown in FIG. 3 at each angle after the coated punch was used as a cold forging die. When almost no exposed base material of the coated punch was observed at each angle, the durability of the coated punch was judged to be good. When a large amount of exposed base material of the coated punch was observed at each angle, the durability of the coated punch was judged to be poor. (Conditions for cold forging test) Cold forging former: "BPF-680SSUL" manufactured by Sakamura Machinery Works, Ltd. Mold: Carbide punch (coated punch of the embodiment or comparative example) Process: 2nd process Construction method: Forward extrusion Processing depth: 110mm Area reduction rate: 50~65% Rotation speed: 40-50 revolutions per minute Material to be formed: Alloy steel Use: Automotive parts Lubrication: Bonded and forged oil (chlorine free) Number of processing: 6000~7000 pieces
[0075] Example 2 In Example 2, a coated punch was manufactured by the same method as in Example 1, except that a cathode having a composition in which the Al content was 70 atomic % and the Cr content was 30 atomic % was used. As in Example 1, various physical properties of the hard coating after coating formation were measured and calculated by the above-mentioned methods for the coated punch manufactured in Example 2. Furthermore, as in Example 1, the surface roughness Ra and surface roughness Ry of the functional part of the coated punch in Example 2 were adjusted as a preparation for the durability test. The measurement and calculation results, as well as the surface roughness values after (after hard coating formation and) polishing (after post-treatment) in Example 2 are summarized in Table 1 below.
[0076] Example 3 In Example 3, a coated punch was manufactured by the same method as in Example 1, except that a cathode having a composition in which the Al content was 80 atomic % and the Cr content was 20 atomic % was used. As in Example 1, various physical properties of the hard coating after coating formation were measured and calculated by the above-mentioned methods for the coated punch manufactured in Example 3. Furthermore, as in Example 1, the surface roughness Ra and surface roughness Ry of the functional part of the coated punch in Example 3 were adjusted as a preparation for the durability test. The measurement and calculation results, as well as the surface roughness values after (after hard coating formation and) polishing (after post-treatment) in Example 3 are summarized in Table 1 below.
[0077] Comparative Example 1 In Comparative Example 1, a hard coating was formed on a punch using a general arc ion plating coating device (manufactured by Kobe Steel, Ltd.) that was equipped with a permanent magnet but no filter mechanism, etc., and a coated punch was manufactured in the same manner as in Example 1, except that the negative bias voltage during coating formation was set to a constant value of 60 V and the arc current during coating formation was set to a constant value of 120 A.
[0078] As in Example 1, various physical properties of the hard film after film formation were measured and calculated by the above-mentioned method for the coated punch manufactured in Comparative Example 1. Furthermore, as in Example 1, the surface roughness Ra and surface roughness Ry of the functional part of the coated punch in Comparative Example 1 were adjusted as a preparation for the durability test. However, the surface roughness Ra immediately after the hard film formation in Comparative Example 1 was as rough as 0.25 μm, and even if the same polishing treatment (post-treatment) as in Example 1 was performed, for example, the surface roughness Ra after the polishing treatment (post-treatment) was a value exceeding 0.05 μm. The measurement and calculation results in Comparative Example 1, as well as the surface roughness value after the polishing treatment (post-treatment) (after the hard film formation) are summarized in Table 1 below. Thereafter, as in Example 1, the durability of the coated punch in Comparative Example 1 was also evaluated. The evaluation results of the coated punch in Comparative Example 1 will be summarized later together with other Examples and Comparative Examples.
[0079] Comparative Example 2 In Comparative Example 2, a coated punch was manufactured by the same method as in Comparative Example 1, except that a coating was formed using two cathodes: one having an Al content of 62 atomic % and a Cr content of 38 atomic %, and the other having an Al content of 50 atomic % and a Ti content of 50 atomic %. Specifically, in Comparative Example 2, unlike Comparative Example 1, the coating had a structure including a first layer made of AlTiN formed on the surface of the functional part of the punch as the substrate (the average composition of the metal elements contained in the hard coating of the first layer was 50 atomic % Al and 50 atomic % Ti), a second layer made of AlTiN and AlCrN formed on the first layer (the average composition of the metal elements contained in the hard coating of the second layer was 56 atomic % Al, 25 atomic % Ti, and 19 atomic % Cr), and a third layer made of AlCrN formed on the second layer (the average composition of the metal elements contained in the hard coating of the third layer was 62 atomic % Al, and 38 atomic % Cr). The coating time was adjusted so that the thickness ratio of each layer was 1 (first layer):3 (second layer):1 (third layer).
[0080] As in Example 1, various physical properties of the hard film after film formation were measured and calculated by the above-mentioned method for the coated punch manufactured in Comparative Example 2. Furthermore, as in Example 1, the surface roughness Ra and surface roughness Ry of the functional part of the coated punch in Comparative Example 2 were adjusted as a preparation for the durability test. However, the surface roughness Ra immediately after the hard film formation in Comparative Example 2 was as rough as 0.20 μm, and even if the same polishing treatment (post-treatment) as in Example 1 was performed, for example, the surface roughness Ra after the polishing treatment (post-treatment) was a value exceeding 0.05 μm. The measurement and calculation results in Comparative Example 2, as well as the surface roughness value after the polishing treatment (post-treatment) (after the hard film formation) are summarized in Table 1 below. Thereafter, as in Example 1, the durability of the coated punch in Comparative Example 2 was also evaluated. The evaluation results of the coated punch in Comparative Example 2 will be summarized later together with other Examples and Comparative Examples.
[0081] Table 1 below shows the physical properties of the hard coating in the coated punches of Examples 1 to 3 and Comparative Examples 1 to 2. The hard coatings of the coated punches of Examples 1 to 3 and Comparative Examples 1 to 2 did not contain any residual inert gas (specifically, argon gas). FIG. 4 shows cross-sectional images of the observation surface of each angle of the coated punch after the cold forging test in Example 1. FIG. 5 shows cross-sectional images of the observation surface of each angle of the coated punch after the cold forging test in Example 2. FIG. 6 shows cross-sectional images of the observation surface of each angle of the coated punch after the cold forging test in Example 3. FIG. 7 shows cross-sectional images of the observation surface of each angle of the coated punch after the cold forging test in Comparative Example 1. FIG. 8 shows cross-sectional images of the observation surface of each angle of the coated punch after the cold forging test in Comparative Example 2.
[0082] [Table 1]
[0083] As shown in Table 1 above, the coated punches in Examples 1 to 3 had low surface roughness Ra values and good surface smoothness not only after polishing (post-treatment) was performed after hard coating formation, but also immediately after hard coating formation. In addition, as shown in Figures 4 to 6, the coated punches in Examples 1 to 3 had almost no exposure of the base material of the punch at any angle after the cold forging test, and therefore had good durability.
[0084] On the other hand, as shown in Table 1 above, the coated punches in Comparative Examples 1 and 2 had high values of surface roughness Ra of the hard coating, and even after polishing (post-treatment) was performed after the formation of the hard coating, the surface roughness Ra of the hard coating remained high, and the surface smoothness was poor. Also, as shown in FIG. 7, the coated punch in Comparative Example 1 had poor durability because about 600 μm of the punch base material was exposed at 0°, where the punch base material was most exposed, after the cold forging test. Also, as shown in FIG. 8, the coated punch in Comparative Example 2 had about 300 μm of the punch base material exposed at 270°, where the punch base material was most exposed, after the cold forging test. That is, the coated punch in Comparative Example 2 also had poor durability.
[0085] 2. Formation of hard coating on test piece made of SKD material In Examples 4 to 5, a test piece made of SKD material was used as a substrate instead of a punch, and a hard coating was formed on the test piece to prepare a coated test piece. Furthermore, in Examples 4 to 5, the adhesion between the test piece and the coating was observed as a reference evaluation.
[0086] Example 4 In Example 4, coated test pieces were prepared in the same manner as in Example 1 in the above 1, except that a test piece made of SKD material, an iron-based alloy, was used as the substrate. Furthermore, similar to Example 1 in the above 1, various physical properties of the hard coating after coating formation were measured and calculated for the prepared coated test pieces in Example 4 by the methods described in the above 1. Furthermore, as a reference evaluation, the adhesion between the test pieces and the hard coating was observed for the prepared coated test pieces.
[0087] Example 5 In Example 5, a coated test piece was prepared by the same method as in Example 4, except that a base layer made of CrN was formed between the test piece and the hard coating made of AlCrN. Specifically, a cathode having a composition with a Cr content of 100 atomic % was used, a bias voltage was set to -50 V, and an arc current was set to 150 A, and a base layer made of CrN was formed on the surface of the test piece until the thickness of the coating became 1 μm. Next, a hard coating made of AlCrN was formed on the base layer made of CrN by the same method as the coating method described in Example 1 of 1 above. In detail, a cathode having a composition with an Al content of 75 atomic % and a Cr content of 25 atomic % was used to form the hard coating made of AlCrN on the base layer. The bias voltage was changed (graded) in the range of -70 V to -200 V so that its absolute value gradually increases from the vicinity of the base layer made of CrN to the vicinity of the surface. The arc current was also changed (graded) so that the value gradually increased from the vicinity of the base layer made of CrN to the vicinity of the surface in the range of 70 A to 180 A. At this time, the hard coating made of AlCrN was formed to a thickness of 5 μm.
[0088] As in Example 4, for the coated test piece in Example 5 thus prepared, various physical properties of the hard coating after coating formation were measured and calculated by the method described in 1. Furthermore, for the prepared coated test piece, the adhesion between the test piece and the undercoat layer and between the hard coating were observed as a reference evaluation.
[0089] The following Table 2 shows the physical properties of the hard coatings in the coated test pieces of Examples 4 to 5. Note that the hard coatings of the coated test pieces of Examples 4 to 5 did not contain any residual inert gas (specifically, argon gas).
[0090] [Table 2]
[0091] As shown in Table 2 above, the coated test pieces in Examples 4 and 5 also had low surface roughness Ra values of the hard coating immediately after hard coating formation, and good surface smoothness, even without polishing treatment (post-treatment) after hard coating formation. In addition, in the coated test piece in Example 4, slight peeling of the hard coating was observed in some parts between the test piece and the hard coating. On the other hand, in the coated test piece in Example 5, such peeling of the hard coating was not observed. From this result, it can be seen that when the material of the base material of the mold is made of SKD material, it is preferable to provide a primer layer between the mold and the hard coating from the viewpoint of reliably suppressing the risk of coating peeling.
[0092] This application is based on Japanese Patent Application No. 2023-158820 filed on September 22, 2023, the contents of which are incorporated herein by reference.
[0093] The embodiments and examples disclosed herein should be understood to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims. [Explanation of symbols]
[0094] 1 Punch 2. Functional section 3 Gripping part 4 Upper end
Claims
1. A mold and a hard coating formed on at least a portion of an outer surface of the mold, The hard coating contains a nitride, a carbonitride, an oxide, or an oxynitride of a metal element, In the total amount of the metal elements contained in the hard coating, the Al content is 65 atomic % or more, the Cr content is 15 atomic % or more, and the total content of Al and Cr is 80 atomic % or more and 100 atomic % or less, The surface roughness Ra of the hard coating is 0.05 μm or less, The coated mold has a d value resulting from the (111) plane of the face-centered cubic lattice of the hard coating of 2.25 Å or more and 2.45 Å or less.
2. 2. The coated mold according to claim 1, wherein the hard coating has a surface roughness Ra of 0.02 μm or less.
3. The hard coating is made of a nitride of a metal element, 2. The coated mold according to claim 1, wherein, in a total amount of the metal elements contained in the hard coating, the Al content is 65 atomic % or more and 80 atomic % or less, the Cr content is 20 atomic % or more and 35 atomic % or less, and the total content of Al and Cr is 100 atomic %.
4. 2. The coated mold of claim 1, wherein the mold is for cold plastic working.
5. 2. The coated mold according to claim 1, wherein the mold is a punch for plastically processing a workpiece by colliding with the workpiece.
6. The material of the die is an iron-based alloy or a high-speed tool steel, The coated mold according to claim 1 , further comprising an undercoat layer between the mold and the hard coating.
Citation Information
Patent Citations
Coated mold for plastic working, and method for manufacturing the same
JP2010284710A